Exploring the Quranic Foundations of Islamic Education - Muh. Amin (Al-Ishlah: Jurnal Pendidikan Islam, 2021)
This study elucidates the concept of Islamic education, emphasizing the formation of a well-rounded and holistic individual through various objectives. Seven key aspects of education in Islam are discussed, namely, education in spirituality and morality, education in intellect and knowledge, physical education, psychological education, aesthetic education, skill-based education, and social education. The primary objective of Islamic education is to shape a Muslim who possesses noble character, physical and spiritual health, intelligence, proficiency, and God-consciousness. This concept reflects the view that education in Islam must encompass the entire spectrum of an individual's life, from the spiritual to the social dimensions. The research methodology for this study involves the analysis of Quranic texts to identify verses related to the objectives of Islamic education. Additionally, a literature review of the thoughts of scholars and Islamic sources is used to reinforce the understanding of the concept of Islamic education. This research approach supports a profound comprehension of the objectives of education in Islam and how this concept is reflected in religious teachings and the perspectives of Muslim communities. This study asserts that education in Islam is not confined solely to religious understanding but encompasses all aspects of life. With a deeper understanding of the objectives of Islamic education, it is hoped that better guidance can be provided for the development of an education system that aligns with Islamic values and principles.